Digital marketing strategy for the future - Shuren, T.K. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2021)
In this article, the writer studies the nature and also the goals of digital marketing. The characteristic features of numerical network Internet management are revised according to the relationship to classical management. The creators emphasize: the main thing in the representation of the integrity of communications on the Internet also in the numerical sphere is that they have an equal advertising focus and also bear an integrative look. The advantages and disadvantages of digital marketing are also revealed, the policy of forming this newest stage of management development is considered.
Keywords: marketing; digital marketing; marketing functions; commercial internet; customer; strategy